Analisis Pengembangan Wisata dan Branding Wisata terhadap Occupancy Raja Hotel Samosir Parbaba (Jurnal Manajemen Kreatif dan Inovasi, 2025)
Tourism development plays a vital role in attracting visitors, while destination branding contributes to shaping a positive image and a strong identity for the destination. This study employed a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation involving the hotel owner, manager, and staff. The aim of this research is to analyze the influence of tourism development and destination branding on the occupancy rate at Raja Hotel Samosir Parbaba. The findings reveal that tourism development around Parbaba White Sand Beach has positively contributed to increasing hotel occupancy, particularly through infrastructure improvements and enhancement of local attractions. Meanwhile, the hotel's branding strategies—highlighting Batak local culture, digital promotion, and local wisdom-based guest experiences—have successfully created a unique appeal for tourists. The synergy between tourism development and branding has proven effective in boosting occupancy rates, especially during holiday seasons and local events. This study concludes that integrated tourism development and destination branding not only increase the number of visitors but also strengthen the hotel's position in the tourism industry. Therefore, sustainable tourism development and appropriate branding strategies are essential for enhancing the competitiveness of hotels and the broader hospitality sector in tourist destinations.